Técnicas de aprendizaje y su incidencia en la lectoescritura de los estudiantes del 5to año EGB Unidad Educativa “Manuel Córdoba Galarza”, Ventanas – Los Ríos - Bustamante Plúa, Maykel Steven (2023)
The learning techniques and their incidence in the reading and writing of students lie in the search for techniques and strategies that allow the development of skills in students at an early age; Various factors intervene in this process that allow the formation and obtaining of significant learning in each of the children. Teachers must implement resources that allow students to awaken the reading and writing habit. Indeed, the story is a good resource, since they are full of imagination, creativity and fantasy that allows the student to be interested and see the reading in a fun way. It is important to mention that the teacher is the one who implements resources, strategies and techniques according to the age of the children and the context that is found. The general objective of this research is to analyze learning techniques and their impact on literacy. Thanks to the bibliographic and field research, it was possible to delve into several topics related to the project, where we were able to learn about the current situation that the 5th year of EGB of the Manuel Córdoba Galarza educational unit is going through, concluding that there are students who present a serious problem of literacy in which the techniques and strategies that teachers apply are not relevant, much less have an influence on improving the academic performance of children. Finally, we were able to give recommendations to teachers on the best techniques that can be applied within their classes where not only literacy can be improved, but also inclusive environments are created where students feel safe when participating.